2021
DOI: 10.3389/frvir.2021.641296
|View full text |Cite
|
Sign up to set email alerts
|

Using a Fully Expressive Avatar to Collaborate in Virtual Reality: Evaluation of Task Performance, Presence, and Attraction

Abstract: Avatar-mediated collaboration in virtual environments is becoming more and more prevalent. However, current consumer systems are not suited to fully replicate real-world nonverbal communication. We present a novel avatar system for collaboration in virtual reality, which supports high levels of nonverbal expression by tracking behavior such as body movement, hand gesture, and facial expression. The system was built using camera tracking technology only. Therefore, in contrast to many other high-level tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The findings of the current study are consistent with recent research reporting that interactions with motion captured avatars are generally rated positively by participants (Higgins et al, 2021;Seymour et al, 2021;Wu et al, 2021). However, when asking participants to indicate a preference for either face-to-face or VR we found that face-to-face interaction is preferred by most.…”
Section: Self-reported Experience Of Conversations Face-to-face Compared With a Realistic Motion Avatar In Vr When Getting Acquaintedsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the current study are consistent with recent research reporting that interactions with motion captured avatars are generally rated positively by participants (Higgins et al, 2021;Seymour et al, 2021;Wu et al, 2021). However, when asking participants to indicate a preference for either face-to-face or VR we found that face-to-face interaction is preferred by most.…”
Section: Self-reported Experience Of Conversations Face-to-face Compared With a Realistic Motion Avatar In Vr When Getting Acquaintedsupporting
confidence: 91%
“…Researchers have begun to analyze participant experiences interacting in HMD-based virtual reality with motion-captured avatars in real-time (Latoschik et al, 2017;Pettersson & Sundstedt, 2017;Smith & Neff, 2018;Wu et al, 2019;Seymour et al, 2021;Wu et al, 2021). However, to date no studies have examined experience interacting with a full face and body motion captured avatar.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Qi Sun, New York University, United States Michael-Grigoriou, 2022;Rogers et al, 2022;Roth et al, 2016;Seymour et al, 2021;Thomas et al, 2022;Wu et al, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…Interaction and co-presence are also related. Co-presence can be measured by user engagement with the environment ( Wu et al, 2021 ). When interacting with others, co-presence refers to how one perceives his or her own participation and the participation of others in the interaction ( Tang and Bradshaw, 2020 ).…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%